PENGARUH INDEPENDENSI, INTEGRITAS, DAN OBJEKTIVITAS AUDITOR TERHADAP KUALITAS AUDIT INSPEKTORAT PROVINSI ACEH DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI - Fayza, M Aqshal; Fachruddin, Rudy; Saputra, Mulia; Mahdi, Sayed (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study investigates the relationship between auditor independence, integrity, objectivity, and audit quality. This study's population consisted of all Aceh Inspectorate auditors. Fifty respondents were selected using a non-probability sampling method in conjunction with the census method. Primary data were collected through the distribution of questionnaires. Statistical data were analyzed by SPSS 26 version. This study shows that audit quality is affected simultaneously by independence, objectivity, and integrity. Auditor independence and objectivity affect audit quality, while integrity does not affect audit quality. According to the moderating regression study, auditor ethics moderated the relationship between the effect of independence and integrity on audit quality but does not moderate the effect of objectivity on audit quality.